Meltzer's History of the Federal Reserve - David Laidler (The University of Western Ontario, Department of Economics, 2003)
This review argues that Allan Meltzer's account of the Fed. between 1913-1951 complements Friedman and Schwartz's in their Monetary History. Meltzer emphasises policy making within the System, rather than the evolution of the money supply and its effects on the economy. He stresses the uncertainty of the Fed's independence before the 1951 Accord, and the effects of economic ideas, notably the real bills and Riefler-Burgess doctrines, on policy. Many virtues in the book are noted, and one weakness, a failure to explain why inadequate ideas became dominant within the Fed when sounder alternatives were available in contemporary monetary thought.
Keywords: 330